AN ANALYSIS ON READABILITY LEVEL OF ENGLISH READING TEXTS IN THE ENGLISH TEXTBOOK ENTITLED BAHASA INGGRIS UNTUK SISWA SMA-MA/SMK-MAK KELAS XI BY OTONG SETIAWAN DJ. AND SUPENI - Priscillia Wekes; Paula Rombepajung; Tirza Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This research aimed to analyse the readability level of the reading material in the textbook entitled Bahasa Inggris untuk Siswa SMA-MA/SMK-MAK Kelas XI by Otong Setiawan DJ. and Supeni. Researchers used quantitative methods to analyse the data. The data used in this study is the reading material in the textbook which is more than 100 words. There are fourteen reading texts which were analysed using two readability formulas, namely Flesch Reading Ease and Flesch-Kincaid Grade Level. The results of the calculations of these two formulas showed that, from fourteenth texts, eleventh (78.6%) reading texts are not in accordance to the eleventh grade students. Only three (21.5%) from fourteenth reading texts that are in accordance to students’ level.